Analisis Tipologi Tanda Sign System Berbentuk Stroberi di Kecamatan Junrejo Kota Batu - Faldi Hendrawan (Jurnal Desain Komunikasi Visual Asia, 2017)
Batu city is a tourism city located in East Java. Batu city is an icon of tourism city and Agropolitan because it is supported by geographical location in plateau and flanked by many mountains. The distinction made by the Batu City’s government became more developed, when the Batu City’s government provided an information media facility for the community. One of them is a sign system to be information about signboard house number in the form of strawberry fruit in kecamatan Junrejo, Batu City. The uniqueness of the form Sign system also does not refer to the form of its predecessor which contains only text or writing numbers with a simple box frame. Inside the structure of the strawberry sign system the selection of strawberry shape objects as the home identity number indicates that there is an interesting distinction of the object to be studied. Visual semiotics perspective will be better able to dissect the existing sign structure on the strawberry sign system. The sign analysis is referred to using the Pierce tradition with one of the typology of iconic, index and symbols. Using the analysis of typology of signs based on the sign connection with the object referred, so the question of background selection and object selection related not with identity that can represent the city of Batu either the condition of the region, government program or community appreciation.